Determination of conversion rate values to characterise the ethanol production of the Kluyveromyces marxianus CBS712 fungus branch - Erdei, Éva; Pócsi, István; Molnár, Mónika; Gyémánt, Gyöngyi; Nagy, János (Acta Agraria Debreceniensis, 2010)
The ethanol production of the Kluyveromyces marxianus CBS712 strain was investigated among different kind of condition. We defined the conversion rate in order to know the efficiency of the ethanol production. To determine this value, it is crucial to characterize the residual glucose concentracio. We chose two method to determine the amount of residual glucose. The first method is the thin layer chromatography (TLC) and the second method is the method of the glucose-oxidase enzyme. We found that the TLC method is reliable than the other method. The conversion rates were determined from these values and the ethanol values. The maximal ethanol production of the characterized Kluyveromyces marxianus CBS712 strain (5.6% (v/v) ethanol at 45 °C, 55.3% conversion rate) is comparable to those strains which are applied in industrial ethanol production nowadays.